Penentuan Sebaran Reservoar Menggunakan Atribut Seismik Pada Lapangan “Cemara” Cekungan Sumatera Tengah, Riau - Zalwi, Eka Nadila; Namigo, Elistia Liza; Azlin, Amalia (Universitas Andalas, 2025)
A research has been carried out to determine the distribution of reservoirs in the